2007
DOI: 10.1103/physrevb.76.113302
|View full text |Cite
|
Sign up to set email alerts
|

Transport through a multiply connected interacting mesoscopic system using the Keldysh formalism

Abstract: We apply the Keldysh formalism in order to derive a current formula easy to use for a system with many sites, one of which is interacting. The main technical challenge is to deal with the lesser Green function. It turns out that, in the case of the left-right symmetry, the knowledge of the lesser Green function is not necessary and an exact current formula can be expressed in terms of retarded Green functions only. The application is done for a triangular interferometer which gives a good account of the Fano-K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
(35 reference statements)
1
19
0
Order By: Relevance
“…Such approximation is called the Ng's ansatz 32,33 . Although it might be be simple and handy, its validity is far from clear.…”
Section: B Multi-terminal Current and Current Conservationmentioning
confidence: 99%
“…Such approximation is called the Ng's ansatz 32,33 . Although it might be be simple and handy, its validity is far from clear.…”
Section: B Multi-terminal Current and Current Conservationmentioning
confidence: 99%
“…There are, however, only a few papers on the Kondo phenomenon in electronic transport through triple-dot structures. [29][30][31][32][33][34][35] Such complex dot systems are of current interest from both fundamental and application points of view. Especially the interference effects in electronic transport attract much attention, as the multidot systems offer a unique possibility to study fundamental phenomena which were earlier observed in solid-state physics and/or quantum optics.…”
Section: Introductionmentioning
confidence: 99%
“…This interferometer-like geometry allows observation of such quantum phenomena like the Aharonov-Bohm oscillations and the Fano antiresonance 1,2,3,4,5,6,7,8,9,10,11,12,13 . Conductance of systems consisting of three or more QDs reveals further interesting features of quantum transport 14,15,16,17,18,19,20,21,22,23,24 . Of particular importance seems to be the interference phenomenon 25,26,27,28,29 , which resembles the well known Dicke resonance in atomic physics 30,31,32 .…”
Section: Introductionmentioning
confidence: 99%